Analisis Pengendalian Kualitas Produk Menggunakan Metode Seven Tools Dan Failure Mode And Effect Analysis (FMEA) Pada UMKM Tahu Goreng Bu Tita Kabupaten Garut (Lembaga Pengembangan Kinerja Dosen, 2025)
UMKM Tahu Bu Tita is a fried tofu production business located in Cihuni Village, Pangatikan District, Garut Regency. In the period 10 November 2024 - 09 December 2024, there was an increase in the number of defective products which caused a financial loss of IDR 3,766,400. The main problem faced by these UMKM is the absence of a structured quality control system and minimal operational standards in the production process, resulting in a high level of product defects. This study aims to identify the causes of product defects and provide suggestions for improvement to improve production quality and process efficiency. The method used in this study is Seven Tools to analyze the type and number of defects, and FAILURE MODE AND EFFECT ANALYSIS (FMEA) to design suggestions for improvement. The results of the analysis showed a total of 9,416 defects, with details of dirty tofu 35%, dry fried tofu 33%, and shredded tofu 32%. Fishbone Diagram shows the main causes come from human, machine, method, and environmental aspects. Although the control diagram shows process stability, there are still variations caused by certain factors. The highest RPN value of 384 was found in tofu defects that were stained due to poor production environment hygiene, while dry fried tofu had an RPN of 240 due to oil temperatures that were too hot and the absence of standard frying procedures. Based on these findings, the proposed improvements include the development of Standard Operating Procedures (SOPs), scheduling regular cleaning of production equipment, improving environmental cleanliness, controlling oil temperature using a thermometer, implementing a shift work system, and using proper frying equipment. These improvements can increase the efficiency of the production process, reduce the number of defective products, and improve overall product quality.